2012
DOI: 10.1007/s12298-012-0110-1
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of selected indigenous rice (Oryza sativa L.) landraces of Rarh Bengal in relation to osmotic stress tolerance

Abstract: A total of ten rare indigenous rice landraces of West Bengal were screened for germination potential and seedling growth under varying concentrations of sodium chloride (NaCl) and polyethylene glycol (PEG) solutions as osmotic stress inducing agents. Among the studied rice landraces Kelas and Bhut Moori showed highest degree of tolerance to induced osmotic stresses. Proline content of the studied lines was also determined. Genetic relationship among the studied rice landraces was assessed with 22 previously re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 13 publications
1
18
0
Order By: Relevance
“…Several workers also reported that these markers are highly polymorphic (Mohammadi-nejad et al 2008;Karmakar et al 2012;Chattopadhyay et al 2014;Ganie et al 2014). The PCR profile obtained from the SSR markers generated a total of 99 alleles including 20 rare alleles and 16 null alleles, accounting an average of 12.37 alleles/ locus which is higher than the numbers reported by other groups using the SSR markers (Mohammadi-Nejad et al 2008;Islam et al 2012;Karmakar et al 2012;Das et al 2013). Based upon the PIC value, amplicon size range and the number of alleles, RM8094 is advocated to be the most useful and informative marker than others for studying the diversity of Saltol QTL.…”
Section: Discussionmentioning
confidence: 99%
“…Several workers also reported that these markers are highly polymorphic (Mohammadi-nejad et al 2008;Karmakar et al 2012;Chattopadhyay et al 2014;Ganie et al 2014). The PCR profile obtained from the SSR markers generated a total of 99 alleles including 20 rare alleles and 16 null alleles, accounting an average of 12.37 alleles/ locus which is higher than the numbers reported by other groups using the SSR markers (Mohammadi-Nejad et al 2008;Islam et al 2012;Karmakar et al 2012;Das et al 2013). Based upon the PIC value, amplicon size range and the number of alleles, RM8094 is advocated to be the most useful and informative marker than others for studying the diversity of Saltol QTL.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, low yield was also associated with a fewer number of spikelets per panicle suggesting that major constraining factor in grain yield was the poor sink capacity. Seedling age induced variation in grain yield and associated traits are also related to cultivars [44]. The cultivar that we used in our study had high tillering potential and wide spacing maintained both in row planting and farmers' practice provided enough room for developing tillers and thus despite super sparsely planting [22], the number of tillers and panicles at harvest was comparable to the optimal densities suggested for HYVs [13].…”
Section: Discussionmentioning
confidence: 63%
“…Consequently, none of the high yielding varieties is resistant to ShB disease neither in Bangladesh nor elsewhere in the world. Fortunately, rice land races have proven to be highly adaptive to diverse environmental conditions and are believed to harbour a number of valuable genetic resources for crop improvement (Karmakar et al, 2012;Roychowdhury et al, 2013;Ganie et al, 2014). Some of the landraces such as Buhjan, Banshpata, Bhasamanik, Nagra Sail, Raghu Sail are tolerant to rice ShB (Dey, 2014).…”
Section: Introductionmentioning
confidence: 99%